2019
DOI: 10.1177/1756287218816595
|View full text |Cite
|
Sign up to set email alerts
|

Should aspirin be suspended prior to robot-assisted radical prostatectomy? A systematic review and meta-analysis

Abstract: Background:Low-dose aspirin use has been correlated with an increased risk of bleeding and overall complications in surgical and invasive diagnostic procedures. In this review, our aim was to analyze the current literature on whether robot-assisted radical prostatectomy (RARP) is feasible and safe in patients taking low-dose aspirin perioperatively.Methods:A systematic review was performed identifying a total of 767 studies, published between January 2000 and September 2017, with five of these studies meeting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Several retrospective studies and one systematic review studied the safety of APs in RARP. According to these studies, continuation of aspirin is not correlated with an increased risk of perioperative surgical morbidity, blood loss, or hospitalization length, with the exception of a slightly higher transfusion rate in these patients (2.6% vs. 1.6%) [7][8][9][10][11][12]. In the present study, there were no cases of transfusion in either the AP or the control group, and the estimated blood loss was lower in both of the AP and the control group compared with that reported previously (Table 4).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Several retrospective studies and one systematic review studied the safety of APs in RARP. According to these studies, continuation of aspirin is not correlated with an increased risk of perioperative surgical morbidity, blood loss, or hospitalization length, with the exception of a slightly higher transfusion rate in these patients (2.6% vs. 1.6%) [7][8][9][10][11][12]. In the present study, there were no cases of transfusion in either the AP or the control group, and the estimated blood loss was lower in both of the AP and the control group compared with that reported previously (Table 4).…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, the management of APs and/or ACs needs to be customized for RARP. However, few studies have evaluated the safety of RARP in patients receiving APs and/or ACs [7][8][9][10][11][12]. Currently, additional information on this subject is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Carneiro et al concluded that continued aspirin use in the peri-operative period does not correlate with an increase in surgical morbidity, blood loss, or hospital length of stay [26].…”
Section: Discussionmentioning
confidence: 99%
“…29 Recent studies in lung, orthopedic and abdominal surgery suggest low or negligible bleeding risk with perioperative continuation of aspirin. [32][33][34][35][36][37][38][39] Recommendations in the facial plastics and dermatologic literature also suggest that continuation of antithrombotic medications is associated with low rates of severe hemorrhagic complications. 8,30,[40][41][42] However, it is important to note that results from other specialties may not be transferable due to the unique risk of vision loss with oculoplastic surgeries.…”
Section: Understanding Surgical Bleeding Riskmentioning
confidence: 99%